Maritime adaptations and dietary variation in prehistoric Western Alaska: Stable isotope analysis of permafrost‐preserved human hair. Issue 3 (17th May 2013) - Britton, Kate; Knecht, Rick; Nehlich, Olaf; Hillerdal, Charlotta; Davis, Richard S.; Richards, Michael P.
ABSTRACT The reconstruction of diet and subsistence strategies is integral in understanding early human colonizations and cultural adaptations, especially in the Arctic—one of the last areas of North America to be permanently inhabited. However, evidence for early subsistence practices in Western Alaska varies, particularly with regards to the emergence, importance, and intensity of sea mammal hunting. Here, we present stable carbon and nitrogen isotope data from permafrost‐preserved human hair from two new prehistoric sites in Western Alaska, providing a direct measure of diet. The isotope evidence indicates a heavy reliance on sea mammal protein among the earlier Norton‐period group (1, 750 ± 40 cal BP), confirming that the complex hunting technologies required to intensively exploit these animals were most likely already in place in this region by at least the beginning of 1st millennium AD. In contrast, analysis of the more recent Thule‐period hair samples (650 ± 40 cal BP; 570 ± 30 cal BP) reveals a more mixed diet, including terrestrial animal protein. Sequential isotope analysis of two longer human hair locks indicates seasonal differences in diet in a single Norton‐period individual but demonstrates little dietary variation in a Thule‐period individual. These analyses provide direct evidence for dietary differences among Alaska's early Eskimo groups and confirm the antiquity of specialized sea mammal hunting and procurement technologies. The results of this study have implications for our understanding of human adaptation to maritime and high‐latitude environments, and the geographical and temporal complexity in early Arctic subsistence. Am J Phys Anthropol 151:448–461, 2013.© 2013 Wiley Periodicals, Inc.